Technology and Equipment for Cold-Chain Storage and Transportation of Fresh Agricultural Products - Yang Tianyang (《中国工程科学》杂志社, 2021)
Technology and equipment for cold-chain storage and transportation is critical for maintaining the quality and improving the circulation efficiency of fresh agricultural products and strategically important for ensuring food safety and increasing agricultural income. In this article, we analyze the demand for cold-chain storage and transportation technology and equipment in China, summarize the current status, and present the gaps between China and developed countries in this regard. Moreover, we clarify the key technologies, key tasks, and major projects for the development of cold-chain storage and transportation technology and equipment for fresh agricultural products using the Delphi method and field research. The major problems faced by technology and equipment include lack of specialized pre-cooling facilities in places of production, lack of refrigerated transportation equipment, backward quick-freezing technology and equipment, lagging research and development of key technologies, non-standardized construction of refrigeration and cold-storage facilities, and insufficient cold-chain infrastructure. Furthermore, we propose a three-step technical route for the development of the technology and equipment: achieving high efficiency and standardization by 2025, informatization and intelligence by 2035, and intelligence and autonomation by 2050.